Analisis Pembuatan Desain Warna pada Kemasan Masker, Shoecover dan Mobcap di PT. Medika Maesindo Global Temanggung Menurut Standar Surat Edaran Alat Kesehatan dalam Negeri untuk Meningkatkan Minat Customer - Muhammad Roqy Murohman; Ari Siswati (Master Manajemen, 2024)
The development of packaging design in Indonesia continues to increase quite significantly, especially in products that are used daily such as packaging and other products in circulation. Nowadays, packaging also functions as a very effective and efficient promotional medium because the information on the packaging will be conveyed directly to consumers when a product is seen or purchased by a consumer. In product packaging design, color changes often occur, where the color changes do not comply with the standards of the AKD (Domestic Medical Devices) circular , which sometimes means designers or related parties may misunderstand or interpret the instructions contained in the Domestic Medical Devices circular. . This can result in color changes that are not as expected. The formulation of the research problem is how to use color in the packaging design for Mask, ShosCover , MobCap products according to the standards of the Domestic Medical Devices circular at PT. Medika Maesindo Global?. The aim of this research is to determine and assess color suitability which involves evaluating whether the colors used in the packaging design comply with the standards of the Domestic Medical Devices circular at PT. Medika Maesindo Global.